Using quantitative single molecule localization microscopy to optimize multivalent HER2-targeting ligands - Wakefield, Devin L.; Golfetto, Ottavia; Jorand, Raphael; Biswas, Sunetra; Meyer, Kassondra; Avery, Kendra N.; Zer, Cindy; Cacao, Eliedonna E.; Tobin, Steven J.; Talisman, Ian J.; Williams, John C.; Jovanovic-Talisman, Tijana (Frontiers in Medicine, 2023)
Introduction The progression-free survival of patients with HER2-positive metastatic breast cancer is significantly extended by a combination of two monoclonal antibodies, trastuzumab and pertuzumab, which target independent epitopes of the extracellular domain of HER2. The improved efficacy of the combination over individual antibody therapies targeting HER2 is still being investigated, and several molecular mechanisms may be in play: the combination downregulates HER2, improves antibody-dependent cell mediated cytotoxicity, and/or affects the organization of surface-expressed antigens, which may attenuate downstream signaling. Methods By combining protein engineering and quantitative single molecule localization microscopy (qSMLM), here we both assessed and optimized clustering of HER2 in cultured breast cancer cells. Results We detected marked changes to the cellular membrane organization of HER2 when cells were treated with therapeutic antibodies. When we compared untreated samples to four treatment scenarios, we observed the following HER2 membrane features: (1) the monovalent Fab domain of trastuzumab did not significantly affect HER2 clustering; (2) individual therapy with either trastuzumab or (3) pertuzumab produced significantly higher levels of HER2 clustering; (4) a combination of trastuzumab plus pertuzumab produced the highest level of HER2 clustering. To further enhance this last effect, we created multivalent ligands using meditope technology. Treatment with a tetravalent meditope ligand combined with meditope-enabled trastuzumab resulted in pronounced HER2 clustering. Moreover, compared to pertuzumab plus trastuzumab, at early time points this meditope-based combination was more effective at inhibiting epidermal growth factor (EGF) dependent activation of several downstream protein kinases. Discussion Collectively, mAbs and multivalent ligands can efficiently alter the organization and activation of the HER2 receptors. We expect this approach could be used in the future to develop new therapeutics.